Tingkat Pengetahuan Masyarakat Mengenai Penggunaan Obat Antihipertensi Golongan Calcium Channel Blocker (Amlodipine) di RT 006 RW 03 Kelurahan Johar Baru Jakarta Pusat - Sakilah Alaisah Astuti; Anna Uswatun Hasanah Rochjana; Milda Rianty Lakoan (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Hypertension is defined as a systolic blood pressure greater than 120 mmHg and a diastolic blood pressure greater than 80 mmHg, measured twice within 5 minutes during rest. If left untreated, hypertension can lead to kidney and heart damage and increase the risk of stroke. This study aims to assess the community's knowledge regarding the use of antihypertensive medication, specifically the calcium channel blocker (amlodipine), in RT 006 RW 03 Kelurahan Johar Baru, Central Jakarta. The study involved 50 participants aged 17-64 years with a history of hypertension. A descriptive quantitative method was used, with data collected through questionnaires and analyzed using SPSS. The results show that 83% of the participants had good knowledge about hypertension, 76% had good knowledge about the dosage of amlodipine, 76% had good knowledge about the correct administration of amlodipine, and 50% had sufficient knowledge about the side effects of the drug. The average knowledge level based on the indicators was 71%, which is categorized as adequate.